Development of Hydrotaea spinigera (Diptera: Muscidae) at Constant Temperatures and Its Significance for Estimating Postmortem Interval. Issue 1 (29th August 2020) - Wang, Yu; Zhang, Yingna; Wang, Man; Hu, Guoliang; Fu, Yangfan; Zhi, Rong; Wang, Jiangfeng
Abstract: Hydrotaea spinigera Stein is a necrophagous species, widely distributed in Oriental and Australasian regions. Considering that the postfeeding larvae or puparia of this species can still be found in abundance at the advanced decomposition stage or even the skeleton stage of remains, it can serve as a good supplementary indicator for estimating the minimum postmortem interval (PMImin ). This could also extend the range of PMImin when the primary colonizers are no longer associated with the corpse or have emerged as adults. This study investigated the development duration, accumulated degree hours, and larval body length changes of H. spinigera at seven constant temperatures ranging from 16 to 34°C, and established three development models for estimating PMImin, including isomorphen diagram, isomegalen diagram, and thermal summation model. At 16, 19, 22, 25, 28, 31, and 34°C, the development durations of H. spinigera from egg to adult stage were 1, 412.6 ± 62.9, 867.4 ± 14.9, 657.1 ± 22.9, 532.3 ± 10.1, 418.8 ± 21.3, 379.8 ± 16.6, and 340.0 ± 20.3 h, respectively. The lower developmental threshold L 0 was estimated as 10.50 ± 0.20°C, and the thermal summation constant K was 7, 648.83 ± 146.74 degree hours. Using regression analysis, equations were obtained modeling the change of larval body length with time after hatching at different temperatures. This study provided basic data based on the growth and development of H. spinigera for the estimation of PMImin in forensic science.